Quality of life of the children suffering from bronchial asthma - Trojanowska, Alina; Emeryk, Andrzej (Polish Journal of Public Health, 2009)
Introduction. Bronchial asthma is the most frequent chronic respiratory disease in children. Epidemiological data suggest that in some countries the frequency and severity of its course, especially in children, has been increasing. Asthma, like any other chronic disease contributes to the deterioration of quality of life and may impair child’s development. Aim. The purpose of study was to evaluate the quality of life of children suffering from bronchial asthma. Material and methods. The study covered 100 children treated for chronic bronchial asthma at the Pulmonological Outpatient Clinic, Children’s Clinical Hospital, Lublin. The research tools used in the study were: PAQLQ questionnaire, a questionnaire created for the purpose of the study and the analysis of medical records. Results. According to 93% of surveyed children the disease and the treatment contribute to limiting of life activity. Asthma interfered with the emotional life too (95%). Statistic analysis confirmed significant relationship between the severity of disease and the quality of life (p=0.037). Within the last year high percentage of children (77%) required additional treatment for exacerbated asthmatic symptoms. The analysis confirmed significantly negative correlation between the frequency of emergency ambulant treatment and the quality of life (r=-0.332, p